Composition and preparation method of nano suspension
Through the acid-base precipitation method and high-pressure homogenization method, the problems of long grinding time, contamination and organic solvent residues during the preparation of meloxicon nano preparations in the prior art are solved, and a rapid, stable and pollution-free preparation of meloxicon nano suspension is achieved.
Patent Information
- Application Number
- CN202311310743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, when preparing meloxicon nano preparations, there are problems such as long grinding time, loss of grinding media, and the use of organic solvents to cause environmental and human risks, making it difficult to achieve rapid onset and good stability of pharmaceutical preparations.
The acid-base precipitation method-high pressure homogenization method was used to prepare a meloxicon nano suspension by dissolving meloxicon and surfactant in an alkaline solution, then quickly mixing with the acid solution and shearing it through an emulsification disperser, and finally homogenizing it in a high-pressure homogenizer, adding polymer and osmotic pressure regulator to prepare a meloxicon nano suspension.
This method does not require the use of organic solvents, simplifies the production process, avoids the peeling and contamination of the grinding medium, has a short preparation time, is suitable for industrial production, and the prepared meloxicon nano suspension has good stability and is suitable for rapid onset of pharmaceutical preparations.
Smart Images

Figure BDA0004487685010000041 
Figure BDA0004487685010000051 
Figure BDA0004487685010000052
Abstract
Description
Technical Field
[0001] The present invention relates to the field of pharmaceutical preparations, and more specifically to a pharmaceutical composition containing meloxicam and a preparation method thereof. Background Art
[0002] Meloxicam is a selective COX-2 nonsteroidal anti-inflammatory drug with analgesic, anti-inflammatory and antipyretic effects. These effects are believed to be related to the inhibition of the COX-2 pathway and the subsequent reduction in prostaglandin synthesis. Meloxicam belongs to the BCS class II drug, is poorly soluble in water, and has a slow onset of oral absorption.
[0003] Nanocrystal technology is a pharmaceutical technology that improves the solubility and dissolution rate of poorly soluble drugs. This technology does not require the use of drug carriers, only a small amount of stabilizers, and no restrictions on encapsulation rate and drug loading. Because the drug particle size is reduced to the nanometer level and the specific surface area is greatly increased, the solubility and dissolution rate of the drug are greatly improved. There are two main methods for preparing nanocrystals. One is to reduce large drug particles to nanometer-scale particles through mechanical force, that is, top-down technology, such as media grinding method, high-pressure homogenization method, etc. The second is to precipitate drug nanocrystals from the supersaturated solution of the drug, that is, bottom-up technology, such as solvent-antisolvent precipitation method, supercritical fluid method, solvent evaporation and spray drying method, etc.
[0004] BAUDAX Bio of the United States has developed a meloxicam nanosuspension using a media grinding method, with the trade name ANJESO, which provides rapid and continuous treatment for acute pain through intravenous administration. CN10996355B discloses a method for preparing meloxicam nanoparticles, which is prepared by media grinding, using grinding beads for grinding, and the grinding time is 6 to 8 hours. The advantages of the media grinding method are that it is widely used, simple to operate, has no restrictions on drug selection, and the difference between different batches of samples is small. However, the disadvantage of this method is that the grinding time is long, and the grinding process uses grinding media grinding beads, which are usually zirconium oxide or polystyrene-coated zirconium oxide materials. The grinding beads will wear out during use, and some detached materials remain in the suspension, which eventually leads to product contamination and affects product quality. The polystyrene particles detached from the grinding beads are controlled in the ANJESO listing application materials.
[0005] CN114652678A discloses a method for preparing a poorly soluble drug nanosuspension, wherein the poorly soluble drug in the implementation case includes meloxicam. The preparation method is a solvent-antisolvent precipitation method, wherein under the action of ultrasound, an organic phase of meloxicam dissolved in DMSO is added to an aqueous phase containing a stabilizer to obtain a suspension, and the obtained nanosuspension is centrifuged and replaced with purified water to remove the organic solvent. The precipitation method is the most common bottom-up method, which is relatively simple and has low equipment cost, but an organic solvent is introduced during operation. The common method for removing organic solvents is centrifugal replacement, and the removal step not only increases the complexity of the process, but also makes the crystals after centrifugal precipitation easily aggregate and agglomerate, and has poor redispersibility. At the same time, the residual organic solvent has an adverse effect on the human body and the environment.
[0006] Therefore, how to develop a meloxicam nanoformulation that is fast-acting and stable through a simple, low-cost, and pollution-free preparation method is a difficult problem to be solved in the prior art. Summary of the invention
[0007] In a first aspect, the present invention provides a method for preparing a meloxicam nanosuspension, the method comprising the following steps:
[0008] (1) dissolving meloxicam and a surfactant in an alkaline solution to prepare an alkaline phase, and using an acidic solution as an acid phase;
[0009] (2) the acid phase and the base phase are quickly mixed, and the mixture is immediately sheared by an emulsifier disperser to obtain a primary mixed solution;
[0010] (3) placing the primary mixed liquid in a high-pressure homogenizer for homogenization to obtain a crude suspension;
[0011] (4) Add the polymer and the optional osmotic pressure regulator to the crude suspension and stir evenly to obtain the finished meloxicam nanosuspension.
[0012] Preferably, in the preparation method, the alkaline solution is an aqueous solution of sodium hydroxide.
[0013] Preferably, in the preparation method, the acidic solution is an aqueous hydrochloric acid solution.
[0014] Preferably, the surfactant may be one or more of a cationic surfactant, an anionic surfactant, a nonionic surfactant or a zwitterionic surfactant;
[0015] Further preferably, the cationic surfactant is selected from one or more of chitosan, cationic phospholipids, and hexadecyltrimethylammonium bromide.
[0016] Further preferably, the anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium deoxycholate, sodium cholate, and docusate sodium.
[0017] Further preferably, the nonionic surfactant is selected from one or more of Tween 20, Tween 80, Span 20, poloxamer, 15-hydroxystearate polyethylene glycol, polyethylene caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer, and vitamin E succinate polyethylene glycol ester.
[0018] Further preferably, the zwitterionic surfactant is selected from one or more of lecithin, globulin, and gelatin.
[0019] Further preferably, the surfactant is selected from one or more of poloxamer 188, poloxamer 338, poloxamer 407, Span 20, Tween 20, Tween 80, 15-hydroxystearate polyethylene glycol, polyethylene caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer, and sodium deoxycholate; further preferably, the surfactant is selected from one or more of Tween 20, Tween 80, and sodium deoxycholate; most preferably, the surfactant is selected from Tween 20 or sodium deoxycholate.
[0020] Preferably, in the preparation method, the polymer is selected from one or more of povidone, vinyl pyrrolidone-vinyl acetate copolymer (PVP / VA), hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and polyethylene glycol; further preferably, the polymer is povidone.
[0021] Preferably, in the preparation method, the osmotic pressure regulator is one or both of sodium chloride and sucrose.
[0022] Preferably, the concentration of the alkaline solution is 0.01 to 0.2 mol / L, preferably 0.05 to 0.15 mol / L, more preferably 0.08 to 0.12 mol / L, and most preferably 0.1 mol / L.
[0023] The concentration of the acidic solution is determined according to the volume ratio of the acid-base phase and the concentration of the alkaline solution, so that the molar ratio of the acid to the base is 1:1.
[0024] Preferably, in step (2), the temperature of the acid phase and the base phase is 4 to 25°C, more preferably 4 to 10°C, most preferably 4°C.
[0025] Preferably, in step (2), the volume ratio of the acid-base phase is 1:5 to 1:20, preferably 1:10 to 1:20, and most preferably 1:10.
[0026] Preferably, in step (2), the shearing speed is 9000 rpm to 18000 rpm; preferably 15000 rpm to 18000 rpm; most preferably 15000 rpm.
[0027] Preferably, in step (3), the homogenization temperature is 5-45°C, preferably 15-45°C, more preferably 25-45°C, more preferably 25-35°C, and most preferably 25°C; the homogenization pressure is 10000-25000psi, preferably 15000-25000psi, preferably 18000-22000psi, and most preferably 20000psi; the homogenization times are 5-20 times, preferably 10-20 times, preferably 15-20 times, preferably 13-17 times, and most preferably 15 times.
[0028] Preferably, in the alkaline phase solution, the concentration of meloxicam is 1-20 mg / ml, preferably 10-20 mg / ml, most preferably 12-15 mg / ml.
[0029] Preferably, in the alkaline phase solution, the mass ratio of meloxicam to the surfactant is 2:1 to 20:1, preferably 8:1 to 16:1, more preferably 8:1 to 12:1, and most preferably 10:1.
[0030] Preferably, the mass ratio of meloxicam to the polymer in the meloxicam suspension is 1:3 to 40:3, preferably 5:3 to 20:3, more preferably 6:3 to 15:3, even more preferably 8:3 to 12:3, and most preferably 10:3.
[0031] The osmotic pressure regulator can be added or not and the amount of addition can be determined according to the requirements (such as whether the suspension is isotonic).
[0032] The object of the present invention also includes providing a meloxicam nanosuspension, characterized in that the suspension is prepared by the above-mentioned preparation method.
[0033] In the meloxicam nanosuspension of the present invention, the average particle size of the meloxicam particles is less than 1000 nm, for example, less than 800 nm, preferably less than 500 nm, more preferably less than 200 nm, and most preferably less than 120 nm.
[0034] Unless otherwise specified, the term "w / v" used herein refers to the weight (in g) of the ingredient contained per 100 mL of a liquid system, ie, g / 100 mL.
[0035] In order to provide a more concise description, some quantitative data herein do not use the term "about". It should be understood that, whether the term "about" is used explicitly or not, each numerical value given here not only includes the actual given value (given value), and it is also meant to include the approximate value of this given value reasonably inferred by a person of ordinary skill in the art, including the equivalent and approximate value of this given value produced due to experimental and / or measurement conditions. In some embodiments, the approximate value is obtained by rounding off based on the measured value or the calculated data based on the measured value. In some embodiments, the approximate value is preferably ± 20%, ± 15%, ± 10%, ± 8%, ± 6%, ± 5%, ± 4%, ± 3%, 2%, ± 1% on the basis of the given value.
[0036] The preparation method of meloxicam nano suspension provided by the present invention uses an acid-base precipitation method-high-pressure homogenization method and has five significant advantages: 1. It does not need to use an organic solvent, thus overcoming the problem of organic solvent residue in a common solvent-antisolvent method preparation process; 2. Sodium chloride generated in a mixing process does not need to be removed and can be used as an osmotic pressure regulator, and there is no organic solvent removal step, thus simplifying the production process; 3. The problem of grinding media falling off and contaminating the product in a medium grinding process can be avoided; 4. The preparation time is much shorter than that of a medium grinding process, and is suitable for industrial production; 5. The meloxicam nano suspension prepared by the method can be sterilized and filtered, and the product has good stability. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still fall within the scope of protection of the present invention. At the same time, the raw and auxiliary materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0038] The sources of raw materials and instruments used in the present invention are as follows:
[0039] Meloxicam (CAS: 71125-38-7, Shandong Xinhua Pharmaceutical Co., Ltd.);
[0040] Multifunctional emulsifying and dispersing machine (model: Magic LAB, IKA company);
[0041] High pressure homogenizer (model: M-110EH, Microfluidis);
[0042] Nanoparticle size Zeta potential analyzer: (Model: Nano ZS, Malvern)
[0043] Example 1 Screening of surfactants in meloxicam nanosuspension
[0044] Meloxicam and surfactant are dissolved in 0.05 mol / L sodium hydroxide solution to obtain an alkaline phase, wherein the concentration of meloxicam is 0.5% (W / V), the concentration of surfactant is 0.2% (W / V), 8 surfactants are selected, see Table 1, and the acid phase is 0.5 mol / L hydrochloric acid solution. The temperature of the acid-base phase is 25°C, and the above acid phase and alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10. The mixture is immediately sheared by a multifunctional emulsifying disperser with a shear speed of 9000 rpm to obtain a primary mixed liquid. The primary mixed liquid is placed in a high-pressure homogenizer and homogenized 20 times at 25°C and 15000si to obtain a crude suspension. Povidone K12 and osmotic pressure regulator sucrose are added to the crude suspension at concentrations of 0.14% (W / V) and 0.91% (W / V), respectively, and stirred evenly. The initial particle size and stability of meloxicam nanosuspension were used as the evaluation indexes to compare the stability of each formulation to determine the optimal surfactant. The specific results are shown in Table 1.
[0045] Table 1: Experimental results of surfactant screening
[0046]
[0047]
[0048] The test results show that among the 8 surfactants preliminarily screened, the initial particle size of the suspension prepared by Tween 20, Tween 80, HS-15, and sodium deoxycholate is small, and the particle size stability at room temperature and accelerated at 40°C is good. The initial particle size of the suspension prepared by Poloxamer 188 and Span 20 is large. The suspension prepared by Poloxamer 338 and Poloxamer 407 is unstable at room temperature and accelerated at 40°C. Comprehensive comparison, Tween 20, Tween 80, and sodium deoxycholate are preferred surfactants. Tween 20 and sodium deoxycholate are most preferred.
[0049] Example 2 Screening of Meloxicam Concentration in Meloxicam Nanosuspension
[0050] Meloxicam and sodium deoxycholate are dissolved in 0.1 mol / L sodium hydroxide solution to obtain an alkaline phase, wherein the concentration of sodium deoxycholate is 0.15% (W / V), the concentration of meloxicam is shown in Table 2 below, and the acid phase is 1 mol / L hydrochloric acid solution. The temperature of the acid-base phase is 25°C, the acid phase and the alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10, and the mixture is immediately sheared by a multifunctional emulsifying disperser at a shear speed of 9000 rpm to obtain a primary mixed solution. The primary mixed solution is placed in a high-pressure homogenizer and homogenized 20 times at 25°C and 15000si to obtain a crude suspension. Povidone K12 and sucrose are added to the crude suspension at concentrations of 0.14% (W / V) and 0.91% (W / V), respectively, and stirred evenly. The initial particle size and stability of the meloxicam nanosuspension are used as indicators to screen the meloxicam concentration, and the results are shown in Table 2.
[0051] Table 2: Meloxicam concentration screening results
[0052]
[0053] The test results show that when the concentration of meloxicam is in the range of 0.1-2.0%, as the concentration increases, the initial particle size of the prepared nanosuspension first decreases and then increases. When the concentration is 1.5%, the initial particle size is the smallest, and the nanosuspension with a larger initial particle size grows faster at room temperature and at an accelerated temperature of 40°C. Taking all factors into consideration, the preferred meloxicam concentration is 1.0-2.0%.
[0054] Example 3 Screening of Acid-Base Phase Temperature in Meloxicam Nanosuspension
[0055] Meloxicam and sodium deoxycholate are dissolved in 0.1 mol / L sodium hydroxide solution to obtain an alkaline phase, wherein the concentration of meloxicam is 1.2% (W / V), the concentration of surfactant sodium deoxycholate is 0.12% (W / V), and the acid phase is 1 mol / L hydrochloric acid solution. The acid-base phase temperature is shown in Table 3. The acid phase and the alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10, and the mixture is immediately sheared by a multifunctional emulsifying disperser at a shear speed of 9000 rpm to obtain a primary mixed liquid. The primary mixed liquid is placed in a high-pressure homogenizer and homogenized 20 times at 25°C and 15000si to obtain a crude suspension. Povidone K12 and sucrose are added to the crude suspension at concentrations of 0.33% (W / V) and 2.18% (W / V), respectively, and stirred evenly. The initial particle size and stability of the meloxicam nanosuspension are used as indicators to screen the acid phase and alkaline phase temperatures, and the results are as follows.
[0056] Table 3: Acid phase and base phase temperature screening results The results show that as the acid-base phase temperature decreases, the initial particle size of the prepared nanosuspension gradually decreases, and the particle size stability at room temperature and accelerated at 40°C for 10 days is good. Therefore, the preferred acid-base phase temperature is 4-10°C, and 4°C is most preferred.
[0057] Example 4 Screening of the Acid Phase and Alkaline Phase Comparison in Meloxicam Nanosuspension
[0058] Meloxicam and sodium deoxycholate are dissolved in 0.1 mol / L sodium hydroxide solution to obtain an alkaline phase, wherein the concentration of meloxicam is 1.5% (W / V), the concentration of surfactant sodium deoxycholate is 0.15% (W / V), and the acid phase is a hydrochloric acid solution, and the specific concentrations are shown in the table below. The temperature of the acid-base phase is 25°C, and the acid phase and the alkaline phase are quickly mixed through a three-way according to the volume ratio in Table 4. The mixture is immediately sheared by a multifunctional emulsifying disperser with a shear speed of 9000rpm to obtain a primary mixed liquid. The primary mixed liquid is placed in a high-pressure homogenizer and homogenized 20 times at 25°C and 15000si to obtain a crude suspension. Povidone K12 and sucrose are added to the crude suspension at concentrations of 0.41% (W / V) and 2.73% (W / V), respectively, and stirred evenly. The volume ratio of the acid phase and the alkaline phase is optimized with the initial particle size and stability of the meloxicam nanosuspension as indicators, and the results are shown in Table 4.
[0059] Table 4: Screening results of volume ratio of acid phase and base phase From the above results, it can be seen that as the volume ratio of the acid phase to the base phase increases, the initial particle size of the suspension decreases, but the rate of decrease slows down. When the volume ratio is 1:10, 1:15, and 1:20, there is no difference in the initial particle size, and the stability is good at room temperature and accelerated conditions of 40°C. Therefore, the volume ratio of the acid phase to the base phase is preferably 1:10 to 1:20. Considering time and production cost, the volume ratio of the acid phase to the base phase is most preferably 1:10.
[0060] Example 5 Screening of shear speed
[0061] Meloxicam and sodium deoxycholate are dissolved in 0.1 mol / L sodium hydroxide solution to obtain an alkaline phase, wherein the concentration of meloxicam is 1.5% (W / V), the concentration of surfactant sodium deoxycholate is 0.15% (W / V), and the acid phase is a 1.0 mol / L hydrochloric acid solution. The temperature of the acid-base phase is 25°C, the acid phase and the alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10, and the mixture is immediately sheared by a multifunctional emulsifying disperser, and the shear speed is as shown in Table 5 to obtain a primary mixed liquid. The primary mixed liquid is placed in a high-pressure homogenizer and homogenized 20 times at 25°C and 15000si to obtain a crude suspension. The homogenized suspension is added with povidone K12 and sucrose at concentrations of 0.41% (W / V) and 2.73% (W / V), respectively, and stirred evenly. The shear rate is screened with the initial particle size and stability of the meloxicam nanosuspension as indicators, and the results are as follows.
[0062] Table 5: Shear speed screening results
[0063]
[0064] The test results show that as the shear speed of the multifunctional emulsifying disperser increases, the initial particle size of the prepared nanosuspension gradually decreases and a plateau phase appears. Therefore, the shear speed is preferably 15000-18000 rpm. Considering the particle size stability results, the most preferred shear speed is 15000 rpm.
[0065] Example 6 Screening of homogenization temperature
[0066] Meloxicam and sodium deoxycholate are dissolved in 0.1 mol / L sodium hydroxide solution to obtain the alkaline phase, wherein the concentration of meloxicam is 1.5% (W / V), the concentration of surfactant sodium deoxycholate is 0.15% (W / V), and the acid phase is 1.0 mol / L hydrochloric acid solution. The temperature of the acid-base phase is 25°C, the acid phase and the alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10, and the mixture is immediately sheared by a multifunctional emulsifying disperser at a shear speed of 9000 rpm to obtain a primary mixed liquid. The primary mixed liquid is placed in a high-pressure homogenizer and homogenized 20 times at 15000si to obtain a crude suspension. The homogenization temperature is shown in Table 6. Add povidone K12 and sucrose to the homogenized suspension at concentrations of 0.41% (W / V) and 2.73% (W / V), respectively, and stir evenly. The homogenization temperature was screened using the initial particle size and stability of meloxicam nanosuspension. The results are shown in Table 6.
[0067] Table 6: Homogenization temperature screening results
[0068]
[0069] The test results show that as the homogenization temperature increases, the initial particle size of the prepared nanosuspension gradually decreases. When the homogenization temperature exceeds 25°C, the initial particle size reaches a plateau. Therefore, the preferred homogenization temperature is 25-45°C. However, considering the particle size stability results, 25°C is most preferred.
[0070] Example 7 Screening of homogenization pressure and homogenization times
[0071] Meloxicam and sodium deoxycholate are dissolved in 0.1 mol / L sodium hydroxide solution to obtain the alkaline phase, wherein the concentration of meloxicam is 1.5% (W / V), the concentration of surfactant sodium deoxycholate is 0.15% (W / V), and the acid phase is 1.0 mol / L hydrochloric acid solution. The temperature of the acid-base phase is 25°C, the acid phase and the alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10, and the mixture is immediately sheared by a multifunctional emulsifying disperser with a shear speed of 9000rpm to obtain a primary mixed liquid. The primary mixed liquid is placed in a high-pressure homogenizer and homogenized at 25°C to obtain a crude suspension. The homogenization pressure and number are shown in Table 7. Povidone K12 and sucrose are added to the crude suspension at concentrations of 0.41% (W / V) and 2.73% (W / V), respectively, and stirred evenly. The initial particle size of the crude suspension is used as an indicator to screen the homogenization pressure and number of times, and the results are as follows.
[0072] Table 7: Screening results of different homogenization pressures and times
[0073]
[0074] From the above results, it can be seen that with the increase of homogenization pressure, the initial particle size of the crude suspension decreases, but when the mean pressure reaches above 15000psi, the decrease in particle size is not obvious. Under the same homogenization pressure, with the increase of homogenization times, the initial particle size of the suspension decreases, but when the homogenization times exceed 15 times, the decrease in particle size is not obvious.
[0075] The nanosuspensions prepared by homogenization 20 times at different pressures showed no significant difference in stability at 0 day, 10 days at room temperature or 10 days at 40°C.
[0076] Because the homogenization pressure is too high, product leakage is likely to occur. Therefore, based on comprehensive considerations, the preferred homogenization pressure is 20,000 psi and the homogenization times are 15 times.
[0077] Example 8 Screening of prescription process for preparing meloxicam nanosuspension
[0078] Meloxicam and sodium deoxycholate or Tween 20 are dissolved in 0.1 mol / L sodium hydroxide solution to obtain an alkaline phase, wherein the concentration of meloxicam is 1.2% (W / V), the concentration of surfactant sodium deoxycholate or Tween 20 is 0.12% (W / V), and the acid phase is a 1.0 mol / L hydrochloric acid solution. The temperature of the acid-base phase is 4°C, the acid phase and the alkaline phase are quickly mixed through a three-way according to a volume ratio of 1:10, and the mixture is immediately sheared by a multifunctional emulsifying disperser at a shear speed of 15000 rpm to obtain a primary mixed solution. The primary mixed solution is placed in a high-pressure homogenizer and homogenized 15 times at 25°C and 20000si to obtain a crude suspension. Povidone K12 and sucrose are added to the crude suspension at concentrations of 0.33% (W / V) and 2.18% (W / V), respectively, and stirred evenly to obtain a meloxicam nanosuspension. The prescription is shown in Table 8, and the stability and filterability results are shown in Table 9.
[0079] Table 8: Optimal process recipe composition
[0080]
[0081]
[0082] Table 9: Stability and filterability results of meloxicam nanosuspension samples prepared by the optimal formulation process
[0083]
[0084] From the above results, it can be seen that the meloxicam nanosuspension prepared by the optimal prescription and process obtained by screening is relatively stable at room temperature and accelerated 40°C conditions for 10 days, and the suspension can be sterilized and filtered.
Claims
1. A method for preparing a meloxicam nanosuspension, characterized in that: The method comprises the following steps: (1) dissolving meloxicam and a surfactant in an alkaline solution to prepare an alkaline phase, and using an acidic solution as an acid phase; (2) the acid phase and the base phase are quickly mixed, and the mixture is immediately sheared by an emulsifier disperser to obtain a primary mixed solution; (3) placing the primary mixed liquid in a high-pressure homogenizer for homogenization to obtain a crude suspension; (4) Add the polymer and the optional osmotic pressure regulator to the crude suspension and stir evenly to obtain the finished meloxicam nanosuspension.
2. The preparation method according to claim 1, wherein The alkaline solution is a sodium hydroxide solution, and the acidic solution is a hydrochloric acid solution.
3. The preparation method according to claim 1 or 2, wherein: The surfactant is one or more of a cationic surfactant, an anionic surfactant, a nonionic surfactant or a zwitterionic surfactant; Further preferably, the cationic surfactant is selected from one or more of chitosan, cationic phospholipids, and hexadecyltrimethylammonium bromide; Further preferably, the anionic surfactant is selected from one or more of sodium dodecyl sulfate, sodium deoxycholate, sodium cholate, and docusate sodium; Further preferably, the nonionic surfactant is selected from one or more of Tween 20, Tween 80, Span 20, poloxamer, 15-hydroxystearate polyethylene glycol, polyethylene caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer, and vitamin E succinate polyethylene glycol ester; Further preferably, the zwitterionic surfactant is selected from one or more of lecithin, globulin, and gelatin; Further preferably, the surfactant is selected from one or more of poloxamer 188, poloxamer 338, poloxamer 407, Span 20, Tween 20, Tween 80, 15-hydroxystearate polyethylene glycol, polyethylene caprolactam-polyvinyl acetate-polyethylene glycol graft copolymer, and sodium deoxycholate; further preferably, the surfactant is selected from one or more of Tween 20, Tween 80, and sodium deoxycholate; most preferably, the surfactant is selected from Tween 20 or sodium deoxycholate.
4. The preparation method according to claim 1 or 2, wherein The polymer is selected from one or more of povidone, vinyl pyrrolidone-vinyl acetate copolymer (PVP / VA), hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and polyethylene glycol; more preferably, the polymer is povidone.
5. The preparation method according to claim 1 or 2, wherein: The osmotic pressure regulator is one or two of sodium chloride and sucrose.
6. The preparation method according to claim 1 or 2, wherein: The concentration of the alkaline solution is 0.01 to 0.2 mol / L, preferably 0.05 to 0.15 mol / L, more preferably 0.08 to 0.12 mol / L, and most preferably 0.1 mol / L.
7. The preparation method according to claim 1 or 2, wherein: The molar ratio of the acid in the acidic solution to the base in the alkaline solution is 1:
1.
8. The preparation method according to claim 1 or 2, wherein: In the step (2), the temperature of the acid phase and the alkaline phase is 4 to 25°C, more preferably 4 to 10°C, most preferably 4°C.
9. The preparation method according to claim 1 or 2, wherein: In the step (2), the volume ratio of the acid-base phase is 1:5 to 1:20, preferably 1:10 to 1:20, and most preferably 1:
10.
10. The preparation method according to claim 1 or 2, wherein: In the step (2), the shearing speed is 9000 rpm to 18000 rpm; preferably 15000 rpm to 18000 rpm; most preferably 15000 rpm.
11. The preparation method according to claim 1 or 2, wherein: In the step (3), the homogenization temperature is 5 to 45°C, preferably 15 to 45°C, more preferably 25 to 45°C, more preferably 25 to 35°C, and most preferably 25°C; the homogenization pressure is 10,000 to 25,000 psi, preferably 15,000 to 25,000 psi, preferably 18,000 to 22,000 psi, and most preferably 20,000 psi; the homogenization times are 5 to 20 times, preferably 10 to 20 times, preferably 15 to 20 times, preferably 13 to 17 times, and most preferably 15 times.
12. The preparation method according to claim 1 or 2, wherein: In the alkaline phase solution, the concentration of meloxicam is 1-20 mg / ml, preferably 10-20 mg / ml, and most preferably 12-15 mg / ml.
13. The preparation method according to claim 1 or 2, wherein: In the alkaline phase solution, the mass ratio of meloxicam to the surfactant is 2:1 to 20:1, preferably 8:1 to 16:1, more preferably 8:1 to 12:1, and most preferably 10:
1.
14. The preparation method according to claim 1 or 2, wherein: The mass ratio of the meloxicam to the polymer is 1:3 to 40:3, preferably 5:3 to 20:3, more preferably 6:3 to 15:3, even more preferably 8:3 to 12:3, and most preferably 10:
3.
15. A meloxicam nanosuspension, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 14.
16. The meloxicam nanosuspension according to claim 16, wherein The average particle size of the meloxicam particles in the suspension is less than 1000 nm, for example, less than 800 nm, preferably less than 500 nm, more preferably less than 200 nm, and most preferably less than 120 nm.